The Changing Landscape of Simulation-Based Education. Issue 8 (August 2019) - Morse, CatherineJean; Fey, Mary; Kardong-Edgren, Suzie; Mullen, Ann; Barlow, Melanie; Barwick, Stephanie
Abstract : N/A: Once considered solely as an educational tool in undergraduate education, simulation-based education (SBE) now has many uses. SBE is now embedded in both graduate and undergraduate nursing education programs and has become increasingly accepted practice in hospital orientation and transition-to-practice programs. Newer applications include ongoing professional education, just-in-time training, teamwork development, and systems testing. This article highlights the changing landscape of SBE and describes elements critical to its successful use, including facilitator competencies, the necessity of providing a psychologically safe environment to enable learning, and the importance of addressing other safety concerns, such as the possibility of accidentally introducing simulated equipment and medications into real patient care. Abstract : This article details three foundational concepts of simulation-based education: prebriefing, debriefing, and safety in simulation. It also provides examples of academic, hospital- and health care center-based, and in situ simulation programs.